Suppression Control of Vibration of Induction Motor with Fluctuating Load by Repetitive Control utilizing Acceleration Sensor - Ishida, Muneaki; Higuchi, Shinichi; Hori, Takamasa (The Japan Institute of Power Electronics, 1994)
In the case that induction motors are applied to the drive of compressors, pumps, and so on, the V/F control of induction motor is usually employed because it is difficult to install speed sensors on the motor or load due to durability of the sensors, structural restriction, etc., and accurate speed control is not required. In such cases, the rotational speed of the motors is considerably fluctuated and the motor frame is vibrated due to the pulsating load torque. When frequency of the torque pulsation is close to the resonant frequency of the mechanical system, large vibration and acoustic noise are produced. In this paper, authors propose a method to suppress the vibration of the V/F controlled induction motor with a fluctuated load by repetitive control utilizing acceleration sensor. It is easy to install the acceleration sensor on the motor or load frame. Because the load torque varies periodically, the repetitive control is considered effective for suppression of the vibration. Effectiveness of the proposed method is confirmed by approximate analysis and experiments.